Atraso de linguagem: do olhar a criança para o escutar a mãe - Rahal, Carina (2008)
When discussing the Language Delay, the Speech and Language Therapy disposes of approaches about the origin, diagnosis and treatment, based on either studies that conceive the language as a response to the organic functioning, or the ones that more recently, made an option to define the language as concomitant to the subjective functioning. However, all of them share two points: that the delay is a language symptom related to what is out of time, after time; and that the focus of the therapy is the child, seen as the one who carries the symptom. The objective of this paper is to present a speech-language therapeutical proposal that has its focus on the mother, so elected as a consequence of her discourse, in which is present the symptom that she attributes to her daughter. To be able to present the symptom, the displacement and the symptom erasure from the mother s discourse, the Discourse Analysis of the French line was applied. The knowledge that came from the Lacanian Psychoanalysis was applied, aiming to point out the importance of the maternal speech in the constitution of a discursive subject (le sujet), the daughter. The knowledge accumulated by the Speech-Language Therapy completed the therapy proposal base of a mother whose sayings were collected, transcripted and analyzed. In the absence of similar papers, it is possible to affirm that this paper will make available an innovating clinical proposal, that is based on the listening that recognizes if the symptom that emerges in the mother s discourse belongs to the child or if it is a symptom put to the child. From this hearing derives the direction of the treatment